Implementasi Standar Usaha Pondok Wisata di Desa Wisata Pentingsari, Yogyakarta - Sudarmayasa, I Wayan; Noor, M. Fauzan; Sukmana, Eman; Uhai, Sabalius (Jurnal Master Pariwisata (JUMPA); Volume 07, Nomor 01, Juli 2020, 2020)
This article contains the implementation of the Minister of Tourism and Creative Economy (Permenparekraf) Regulation No. 9 of 2014 concerning homestay tourism standards in the management of homestay in pentingsari tourism villages as supporting the existence of tourist attractions in pentingsari tourism villages. The method used in this research is descriptive, namely by collecting data using questionnaires, field observations, literature studies, documentation and interviews with several key informants as resource persons such as chairperson, manager, and owner of the tourist cottage it self. This article describes the suitability of tourist huts in pentingsari tourism village in accordance with Permenparekraf No. 9 of 2014 from three priority aspects, namely management aspects, service aspects and product aspects, which is still not in accordance with the homestay conditions at the pentingsari village. Keywords: Implementation, Standards, Homestay, Tourism Village